Influence of Self-Efficacy, and Perceived Ease Of Use, Perceived Usefulness Behavioral Intention To Purchase Online In Tokopedia With Perceived Risk, As Variable Mediation - Rosa Merry Yusvita; Vera - Pujani (Universitas Madura, 2020)
Abstract: This study aims to determine the effect of self-efficacy, and Perceived Ease of Use, Perceived Usefulness Against Behavioral Intention in TOKOPEDIA Online Purchase Transactions with Perceived Risk, as a mediating variable (Study in Padang City Communities)